PEMASARAN DAN NILAI TAMBAH RUMPUT LAUT DI KABUPATEN TAKALAR, PROVINSI SULAWESI SELATAN - Ummy Qalsum; Andriyono Kilat Adhi; Anna Fariyanti (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
This study was aimed to analyze the marketing performance of seaweed in Takalar District, South Sulawesi and to analyze the value added obtained from seaweed processing into pure carrageenan powder (semi refined carrageenan). The respondents in this study were 100 fishermen, 37  merchants, 3 wholesalers, 2 exporters, and 1 processing industry. Seaweed marketing performance was measured by marketing efficiency with criteria of marketing margin, farmer’s share and profit margin ratio, whereas value added was analyzed using Hayami’s method. Results showed that there were 5 seaweed marketing channels. Based on the analysis of marketing efficiency, it was found that channel 4 was a relatively efficient channel compared to other channels with the lowest margin value and the highest farmer’s share value of 28.95% and 71.05%, respectively, and the distribution of profit margin ratio spread evenly with the total profit margin ratio of 5.23. The value added of seaweed processing into carrageenan powder was Rp 13 979.16 /kg with a ratio of 44% and was classified as a high value added due to its value which was more than 40%